Scale-up behavior of the froth stability measurement - Geldenhuys, Armand Stefan (Centre for Minerals Research, 2019)
Froth flotation is a widely used physio-chemical separation method in the minerals processing industry. Two distinct phases are present, namely: the pulp and froth phase. Flotation research has heavily focussed on the pulp performance; however only recently it was found that the froth performance contributes significantly to the overall flotation performance. Numerous parameters have been investigated to accurately quantify froth performance with the most notably being froth recovery. That being said, experimentally gathering data to obtain froth recovery is challenging and prone to large experimental errors. For this reason, the stability of the froth phase has been highlighted as a possible characterisation tool. Froth stability is defined as the time of persistence of the froth and is usually measured using either a dynamic and/or static methodology. Although measurement of froth stability has become common place in numerous flotation research articles, little to no attention has been given to the scale-up behaviour of the measurement. It is easily thought of that a froth constrained within a froth column will behave significantly different to one in an industrial flotation cell. Two common scale parameters, froth column diameter and initial pulp bubble size, was chosen to illustrate the dependence of the current methodology on scale. This does not mean that there are not vastly more parameters that would affect the measurement (column material of construction and/or column shape); however, these are two of the most easily changed parameters from experimental setup to setup. Four different column diameters were used for this study. Column diameter experiments were done on an industrial scale by means on manual tracking of froth growth versus time. Pulp bubble size experiments was performed on a laboratory scale by using different pore size glass frits while maintaining a constant superficial gas velocity. Dynamic stability for the pulp bubble size experiments were done by means of video tracking of froth growth versus time. The column diameter data sets highlighted similar behaviour – an increase in measured dynamic stability is seen with increasing column diameter up until a maximum is reached. This behaviour was attributed to the fact that wall films are thought to drain much faster than interstitial Plateau borders. As the column diameter decreases, the relative ratio of column surface area to bulk area increases and therefore results in an increased drainage rate a subsequently less stable froth. An empirical relationship was proposed to correct for the column diameter effect which is based on a ratio of bubble size to column diameter. The pulp bubble size data sets highlighted similar behaviour – an exponential decrease in measured dynamic stability is seen with increasing pulp bubble size. This behaviour was attributed to two fundamental mechanisms occurring within larger bubbled froths. Firstly, an increase in drainage rate as well as change in the drainage regime is seen as a function of bubble size; where in general froths of larger bubble sizes drain significantly faster. Secondly, on average froths consisting of large bubbles will have less water per volume of froth due to the decrease in bubble surface area. The effect of water content in a froth is well known and it can be said that wet froths experience less coalescence and bursting events. Therefore, the combination of the two mechanism is put forth as an explanation of the observed behaviour of the experimental systems.